The sense of moral obligation facilitates information agency and culture. (2020) - Maranges, Heather M.; Baumeister, Roy F.; Vohs, Kathleen D.
Abstract: Tomasello argues that humans' sense of moral obligation emerges early in development, relies on a shared "we, " and serves as the foundation of cooperation. This perspective complements our theoretical view of the human self as information agent . The shared "we" promotes not only proximal cooperative goals but also distal ones via the construction of shared understanding – it promotes culture.